French background of Middle Scots literature - Smith, Janet Mary (The University of Edinburgh, 1933)
We have now made a survey of Scottish literature throughout the Middle Ages, bringing together the work or the editors of the middle Scots texts, and of the scholars who have written on various parts of the subject. AL the same time we have tried to indicate, more roughly, the course of the contemporary literature in France. We find that Scotland, like England, looked to France as the chief source of literary culture. The imitation was not always direct; England, and especially Chaucer, made a bridge between France and the North. Political circumstances tended to increase the direct influence, which culminated in the reign of James V and the regency of Mary of Guise - in Lindsay and "The complaynt of Scotlande". Yet there is no intrinsic bond between the two literatures. Scottish authors borrowed their materials and forms from France, but they were never very deeply influenced by the spirit of French courtly poetry, nor by that subtler essence defying analysis, the "esprit gauloise". Scotland is in the position of a pupil, but of a fairly independent pupil. No French writer ever inspired the admiration and reverence which the Makars accorded to Chaucer. The connection with France enabled the Scottish poets to be more independent of English influence and to take their place in European culture, as James IV enabled his country to do politically. This place they held till the end or the Middle Scots period. We can look back on the Scottish Middle Ages as a literary period in many ways imitative, yet fully alive, and richly representative of mediaeval culture; as a period characteristically Scottish in spite of .its literary borrowings, and worthy of the nation to whose life it gave expression.
The French background of Middle Scots literature